Fertility in African communities affected by HIV - Lutalo, Tom; Ssempijja, Victor (MRC/UVRI Research Unit on AIDS., 2011)
Uganda is famous for its success in bringing down HIV levels, but has persistently high fertility: on average women have seven children by the time they finish childbearing. The resulting high rates of population growth are detrimental to development and will make it difficult for high quality health and education services to keep up with the growing population.
Keywords: HIV; AIDS; fertility; family planning; population growth; reproductive health